Understanding SPI in small organizations: a study of Mexican software enterprises. Issue 5 (5th April 2016) - Espinosa‐Curiel, Ismael Edrein; Rodríguez‐Jacobo, Josefina; Fernández‐Zepeda, José Alberto
Abstract: Software process improvement (SPI) has become one of the main strategies employed by small software enterprises to reduce their development costs or to increase the quality of their products and their development speed. Recent studies show that many small organizations still struggle to implement SPI initiatives successfully. One of the main problems with small organizations is that they usually lack the knowledge and practical experience about the human, social, and organizational phenomena associated with SPI initiatives and their effects. The objective of this paper is to present a grounded action research study that investigated SPI initiatives conducted by 10 Mexican small enterprises. The main product of this study is an initial theoretical framework that attempts to explain the effects of SPI initiatives in small organizations. We concluded that SPI initiatives affect organizational elements (i.e., structure, culture, organizational climate, projects) and human resources (i.e., employees and managers), and vice versa, and these elements are highly interrelated. Therefore, small enterprises need comprehensive SPI strategies that consider, in an integrated way, changes in processes, organizational elements, and human resources. SPI practitioners can use the results of this study to define more efficient and effective strategies to implement SPI initiatives in small organizations. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The objective of this paper is to present a grounded action research study that investigated SPI initiatives conducted by 10 Mexican small enterprises. The main product of this study is an initial theoretical framework that attempts to explain the effects of SPI initiatives on small organizations. We concluded that SPI initiatives affect organizational elements (i.e., structure, culture, organizational climate, projects) and human resources (i.e., employees and managers), and vice versa, and these elements are highly interrelated.